Analysis of Dynamic Change and Causes of the Area of Hala Lake from 1986 to 2019 - WANG Renjun; LIU Baokang; HUANG Bingting (Renmin Zhujiang)
The dynamic monitoring of lake area not only contributes to the analysis of regional climate change scenarios,but also provides reliable data sources for regional water resources assessment.Based on the multi-source satellite data from 1986 to 2019,this paper extracts the water area of Hala Lake,and analyzes the inter-decadal,inter-annual and annual dynamic changes and their causes of the Hala Lake in the last 36 years in combination with the observation data of Delingha and Tuole meteorological stations around Hala Lake.The results show that:The area of Hala Lake decreased first and then increased between 1980s and 2010s,among which the area decreased slowly from 1986 to 2001,and then expanded from 2002 to 2019.The average area is the smallest in 1990s and the largest since 2010.Within a year,the lake area first decreased and then increased in the past three years.The lake area in 2019 was larger than that in the previous two years,except in April and December when was about the same as that in 2018,and the difference between the maximum and minimum monthly area in the past three years was 10.08 km2 and 12.52 km2 respectively.The area with obvious changes in the shoreline is located in the southeast and southwest of the Hala lake.After the analysis of meteorological and glacier data,it indicates that the climate in the Hala Lake shows a warming and humidifying trend from 1961 to 2018,with the temperature rising rate of 0.4 ℃/(10a) (R=0.296),and the precipitation increasing rate of 19.3 mm/(10a) (R=0.562,P<0.01).Therefore,it can be concluded that the climate warming and humidifying and the reduction of glacier area together lead to the expansion of the lake area,which is mainly caused by precipitation.